Dukungan Sosial, Optimisme dan Kebahagiaan pada Mustahiq - Raras Sutatminingsih; Ihya Zaina (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2020)
Happiness is a hope in the lives of many people, including the Mustahiq. This research aims to know the relationship between social support and optimism with happiness at Mustahiq. Participants in this study were 64 Mustahiq Rumah Zakat Medan determined by purposive sampling technique. The scale of research used is the scale of happiness and optimism based on the Seligman theory, and the social support scale based on House theory. The Data on this study was analyzed using multiple linear regression techniques which results in showing a positive relationship between social support and optimism with happiness at Mustahiq with significance value of. 000 which means smaller of. 05. Social support provided an effective contribution to happiness of 30.3% and optimism by 15.5%. This study reveals that high social support and optimism can help mustahiqiq achieve happiness in his life. Therefore, the institution of Amil Zakat is expected to continue to improve the social support given at Mustahiq, especially in giving attention and assistance that is directly perceived by Mustahiq.